Transformasi Manajemen Dakwah Ahmadiyah Di Indonesia: Kajian Atas Adaptasi Organisasi Terhadap Regulasi Dan Stigma Sosial - baharudin ardani; Suparto . (Jurnal Kajian Islam dan Sosial Keagamaan, 2026)
This study examines the management transformation of the Indonesian Ahmadiyya Community (JAI) in response to severe institutional pressures, primarily driven by the 2008 Joint Ministerial Decree (SKB 3 Menteri) and discriminatory local regulations. Employing the P-O-A-C (Planning, Organizing, Actuating, Controlling) management framework and organizational adaptation theory, the analysis focuses on JAI's mechanism for survival amidst legal stagnation and social stigma. The findings indicate that JAI achieved resilience through two core strategies: (1) Strengthening centralized internal management and focusing the actuating function on internal tarbiyat (spiritual training) to build members' psychosocial resilience. (2) Strategic external adaptation by shifting from theological dakwah (bil lisan) to humanitarian service (dakwah bil hal) under the Humanity First banner. While the humanitarian program successfully built a positive narrative and legitimacy, this strategy reflects a managerial trade-off: diverting resources from the core theological mission for survival, suggesting a strategic functional secularization. Theoretically, this study affirms that spiritual conviction serves as a crucial intangible asset for mobilizing human resources within a persecuted minority organization..